Solidification of water in a thermal storage unit equipped with nanoparticle. (1st November 2022) - Hussen, Hasanen M.; Alawee, Wissam H.; Dhahad, Hayder A.; Khalifa, Narjes Turki; Althobaiti, Saad; Hussin, Amira M.
Abstract: As a viable approach for accelerating the freezing process, inclined fins were attached to cold surfaces in this study. The enclosure has two adiabatic surface and two cold ones. The domain was filled with liquid water and due to cold surfaces; it starts to change to solid. In such situation where conduction plays the key role, convection is of secondary importance and can be ignored in mathematical model. With this proposition, two equations remain including unsteady terms and finite element method was applied to attain the solution with involvement of adaptive mesh. Moreover, validation respected to earlier numerical work indicated the reasonable accommodation. By altering the shape parameter to greater value the period of freezing declines around 5.4 %. Also, adding greater volume of platelet nanoparticles makes time to decrease a bit higher than 11 %. Highlights: As a viable approach for accelerating the freezing process were scrutinized. Freezing declines around 5.4 % with augment of m . Adding more nanoparticles makes time to decrease a bit higher than 11 %.